A Historical Perspective on Surgical Manipulation of the Membranous Labyrinth for Treatment of Meniere's Disease - Kersbergen, Calvin J.; Ward, Bryan K. (Frontiers in Neurology, 2021)
Meniere’s disease is an inner ear disorder without a known cause. Endolymphatic hydrops is a swelling of the endolymph spaces that has been observed consistently on post-mortem histology in patients with a history of Meniere’s disease but can occur in asymptomatic individuals and in association with other diseases. Since its discovery, Meniere’s disease has been a disorder managed primarily by otolaryngologists. Surgical treatments, therefore, have accompanied attempts at medical management. Inspired by patients’ sensations of ear fullness and later by the histologic findings of hydrops, surgeons began manipulating the membranous labyrinth to relieve episodes of vertigo while preserving hearing. This review highlights this history of manipulation of the membranous labyrinth. These procedures indicate a rich history of innovation that parallels developments in otologic surgery. The patient studies are uniformly retrospective, with some procedures performed first in animal models. Many approaches were endorsed by eminent otologic surgeons. Surgeries on the endolymphatic sac are performed by some surgeons today; however, procedures on the membranous labyrinth indicated similar symptomatic relief through a minimally invasive procedure, in many cases performed using only local anesthetic. Episodic vertigo in patients with Meniere’s disease is a distressing symptom, yet spontaneous remissions are common. The reports of procedures on the membranous labyrinth reviewed here consistently indicated fewer vertigo episodes. Variable degrees of hearing loss were common following these procedures, however, and many were abandoned. Additional innovative surgeries are inevitable, but we must understand better the relationship of endolymphatic hydrops to disease pathophysiology and patient symptoms.